Perbandingan Kemampuan Pemecahan Masalah Matematis Siswa antara Problem Centered Learning dan Problem Based Learning - Erik Rinaldi; Ekasatya Aldila Afriansyah (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2019)
This article is based on the fact that problem-solving is a basic skill that every student should possess. To improve the student`s mindset through the effort to find problem-solving independently, so the learning activities should be centered on the students. The purpose of this study is to determine the comparison and improvement of students mathematical problem-solving abilities, as well as student attitudes toward the learning model problem-centered learning and problem-based learning. The research method used was a quasi-experiment with purposive sampling. The first experimental class that was class VIII I that got problem-centered learning model as much as 31 students, and the second experimental class that was class VIII H who got the problem-based learning model as many as 31 students. From the research and statistical calculations result, obtained the conclusion that the mathematical problem-solving ability students who got the model centered learning problem was better than students who got the model of learning problem-based learning. Meanwhile, for improvement of problem-solving abilities of mathematical students who got the learning model problem-centered learning and problem based learning each intermediate interpretation. And generally, the students’ attitude to the learning of mathematics by using the learning model problem-centered learning and problem-based learning are well interpreted.